Branched-Chain Amino Acids Enhance Retinal Ganglion Cell Survival and Axon Regeneration after Optic Nerve Transection in Rats. (2nd December 2018) - Wang, Tao; Wei, Xiao-Yan; Yang, An-An; Liu, Zhao; Wang, Shi-Qi; You, Yi-Yan; Kuang, Fang; You, Si-Wei; Wu, Ming-Mei
ABSTRACT: Purpose : This study's aim was to investigate the beneficial effects of branched-chain amino acids (BCAAs) on the neuronal survival and axon regeneration of retinal ganglion cells (RGCs) after optic nerve (ON) transection. Method : The experimental rats received daily BCAA injections through the caudal vein after left intra-orbital ON transection. Neuroprotection was evaluated by counting Fluorogold-labeled RGCs. The role of mammalian target of rapamycin (mTOR) pathway activation in promoting RGC survival was studied after rapamycin administration. Moreover, a peripheral nerve (PN) graft was transplanted onto the transected ON to study the effects of BCAAs on axon regeneration of injured RGCs. Results : Our results showed that BCAAs alleviated the death of RGCs 7 and 14 days after ON transection, accompanied by an activation of mTOR pathway in RGCs. Blocking mTOR pathway with rapamycin eliminated such neuroprotective effects of BCAAs. Moreover, BCAAs also promoted axon regeneration of injured RGCs into a PN graft. Conclusion : Our results suggest a neuroprotection of BCAAs through the activation of mTOR pathway. BCAAs also have a beneficial effect on axon regeneration of injured RGCs. Therefore, BCAAs could be considered for the clinical treatment of ON injury.